ANALISIS KEBIJAKAN PERLINDUNGAN DATA ANAK DI MEDIA SOSIAL INDONESIA: KAJIAN LITERATUR REGULASI DAN IMPLEMENTASI - Eko Wibisono; Muhammad Japar; Raharjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze child data protection policies on social media in Indonesia and to examine their implementation as well as the challenges encountered in practice. The object of this research is child data protection regulations and their implementation in children’s use of social media in Indonesia. The study adopts a qualitative approach with a normative legal method based on literature review, through the analysis of laws and regulations, academic journals, and policy documents related to the protection of children’s digital data. The findings show that Indonesia has established several regulations, such as the Child Protection Law, the Electronic Information and Transactions Law (ITE Law), the Personal Data Protection Law, and PP TUNAS 2025, which serve as the legal foundation for protecting children’s data in digital spaces. However, the implementation of these regulations still faces various obstacles, including regulatory fragmentation, weak oversight of digital platforms, low public digital literacy, and suboptimal age verification systems and child data protection mechanisms on social media. In conclusion, the protection of children’s data on social media requires a multidimensional approach through strengthened regulations, improved oversight of digital platforms, and enhanced digital literacy among children, parents, and schools. This study recommends the need for regulatory harmonization and collaboration among stakeholders to create a safe digital environment for children.